Pelayanan Kartu Keluarga di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Minahasa * - Irvan Kristanto Banua; Thelma Wawointana; Marthinus Mandagi; Muh Ryan Rahmatul Hidayat (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2023)
This study aims to determine the effectiveness of family card services at the Department of Population and Civil Registration of Minahasa Regency. The research method used in this study is a qualitative method. The results of the research conducted on family card services at the Minahasa Regency Population and Civil Registration Office show that family card services are quite effective. Judging from several indicators, including 1) Service procedures for issuing family cards at the Minahasa Regency Population and Civil Registration Office are quite effective, this is illustrated by service procedures and service flow that are clear and in accordance with existing service mechanisms, 2) Budget/cost at the Department of Population and Civil Registration of Minahasa Regency it has been quite effective, this is illustrated by the existence of a budget and costs available from the government and the realization of the budget that has been carried out is in accordance with what was planned, 3) Achievement of targets/targets in making family card documents, this means that services are effective and according to plan, 4) High work motivation at the Population and Civil Registration Office of Minahasa Regency can be seen from the services provided to the community as much as possible. This illustrates that family card services are quite effective.